First report of Postharmostomum sp. (Witenberg, 1923) (Trematoda, Brachylaemidae) in Megalobulimus maximus (Mollusca, Gasteropoda) from San Martín, Peru - Sánchez, Lidia (2005)
A total of 227 specimens of young adults of Postharmostomum sp., Witenberg, 1923 (Trematoda: Digenea) were collected from pericardial cavity of two indiviudals of the land snail Megalobulimus maximus from distrito of Juanjuí, San Martín. Parasits were deposited on Coleccion Helmintológica y de Invertebrados Relacionados, of the Museo de Historia Natural, Universidad Nacional Mayor de San Marcos (MUSM), Lima, Peru.